Sarah Kane’s Blasted: Examining the Issue of Sexual Assault - Shaaban Sulaiman Sadeeq (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Sarah Kane’s Blasted deals with sensitive issues that generate a lot of controversy. She demonstrates anti-feminism in the play because of the way she has shifted the audience attention away from the sexual turpitude committed against the only female character (Cate) in the play; and how she places emphasis on the sexual abuse inflicted on Ian the male character. Questions that would possibly arise are: what is her insinuation? Is she trying to defend sexual violence against women? Does it mean that men have the right to rape? Why has she not taken sexual violence against the female character serious? Why is attention drawn to the male rape than the female rape? Does Kane try to portray a new view of rape? All these questions and many more could have been streaming through the viewers’ mind. Notwithstanding, this paper attempts to examine the pedigree and degree of sexual misconduct in the Blasted and the reasons that make the writer draw the attention of the audience to the sexual abuse that men undergo rather than the common and popular one against the women. Thus, at the end of the play, the critical eye can make one realize that, Sarah Kane isn’t an anti-feminist person but deep down in her, she cleverly defends women, presenting them as a figure with perseverance, love and strength despite all men’s demonization about them; and this she reflects in Cate’s character.